Grape seed oil supplementation in lamb diet: effect on meat oxidation stability and muscle fatty acids. Issue 1 (2nd January 2019) - Sharifi, Mohammad; Bashtani, Moslem; Naserian, Abbas Ali; Farhangfar, Homayoun; Rasani, Mahin; Emami, Ali
Abstract: The effect of grape seed oil (GSO) on the animal performance, blood metabolites, meat oxidation stability and muscle fatty acids of lambs was evaluated. Eighteen Baluchi lambs, 196 ± 14 days of age and 39.8 ± 1.7 kg body weight were randomly allocated to three dietary treatments: (1) diet without GSO (Control), (2) diet containing 2% GSO (GSO2) and (3) diet containing 4% GSO (GSO4). Results showed that dry matter intake and animal performance were not affected by treatment ( p  > .05). Addition of 4% GSO to diet increased plasma total cholesterol and triglyceride ( p  < .01). Inclusion of GSO to the diets increased ( p  < .001) the proportions of trans -9 C18:1, vaccenic acid (VA), rumenic acid (RA), C18:2 n-6 and polyunsaturated fatty acid (PUFA), while decreased ( p  = .01) the concentration of saturated fatty acid in longissimus lumborum (LL) muscle of lambs. At the same time, dietary GSO increased oxidative stability of LL muscle during the 12 days of storage time ( p  < .0001). In conclusion, these results showed that GSO up to 4% in the lamb diet can improve meat quality by increasing VA, RA, PUFA and oxidative stability in LL muscle lambs without affecting animal performance. Highlights: Grape seed oil (GSO) is rich source of linoleic acid and phenolic content and can consider as a natural antioxidant. GSO increased proportions of Polyunsaturated fatty acid, vaccenic and rumenic acids. GSO increased oxidative stability of muscle during the storage time.